Perbandingan Prestasi Belajar Matematika Siswa dengan Pendekatan CTL Antara Model Pembelajaran Kooperatif Tipe STAD dan NHT ditinjau dari Kepercayaan Diri. - Vera Dewi Susanti (Jurnal Pendidikan Edutama, 2014)
Comparison of Mathematics Learning Achievement of Students with CTL approach between Cooperative Learning Model of STAD Type and NHT viewed from students’ self-confidence. The objective of research is to find out which one providing better achievement, the CTL learning model with STAD, that with NHT or the direct learning model. The population of research was the students of Junior High Schools throughout Madiun Regency in the first semester of VIII grade in the school year of 2011/2012. The sampling technique used was stratified cluster random sampling with the students of SMP Negeri 2 Dolopo, SMP Negeri 2 Kebonsari and SMP Negeri 2 Geger as the sample. Technique of analyzing data used was 3x3 two-way variance analysis. From the result of analysis, it could be concluded that The mathematics learning achievement of students using STAD type of cooperative learning model with CTL approach was better than that using NHT type, that using STAD type with CTL approach was better than that using direct learning model, and that using NHT type with CTL approach was better than that using direct learning model.Keywords: CTL approach, STAD model, NHT, direct learning, self confidence.